Intervention Strategies Based on Information-Motivation-Behavioral Skills Model for Health Behavior Change: A Systematic Review - Sun Ju Chang, RN, PhD; Suyoung Choi, RN, PhD; Se-An Kim, RN, MSN; Misoon Song, RN, PhD (Elsevier, 2014)
Purpose: This study systematically reviewed research on behavioral interventions based on the information-motivation-behavioral skills (IMB) model to investigate specific intervention strategies that focus on information, motivation, and behavioral skills and to evaluate their effectiveness for people with chronic diseases. Methods: A systematic review was conducted in accordance with the guidelines of both the National Evidence-based Healthcare Collaborating Agency and Im and Chang. A literature search was conducted using electronic databases. Randomized controlled trials that tested behavioral interventions based on the IMB model for promoting health behaviors among people with chronic diseases were included. Four investigators independently reviewed the studies and assessed the quality of each study. A narrative synthesis was used. Results: A total of 12 studies were included in the review. Nine studies investigated patients with HIV/AIDS. The most frequently used intervention strategies were instructional pamphlets for the information construct, motivational interviewing techniques for the motivation construct, and instruction or role playing for the behavioral skills construct. Ten studies reported significant behavior changes at the first post-intervention assessment. Conclusion: This review indicates the potential strength of the IMB model as a theoretical framework to develop behavioral interventions. The specific integration strategies delineated for each construct of the model can be utilized to design model-based interventions.